Age-dependent dose conversion coefficients for external exposure to radioactive cesium in soil. Issue 1 (2nd January 2016) - Satoh, Daiki; Furuta, Takuya; Takahashi, Fumiaki; Endo, Akira; Lee, Choonsik; Bolch, Wesley Emmett
Abstract : To estimate effective doses for members of the public exposed to external radiation from radioactive cesium ( 134 Cs and 137 Cs) deposited on the ground by the Fukushima nuclear accident, we calculate the conversion coefficients for converting activity concentration to effective dose rate by using the Particle and Heavy Ion Transport Code System. The data were produced from different age groups within the public (newborns; 1-, 5-, 10-, and 15-year-old children; and adults) for the situations in which radioactive cesium is distributed uniformly in the soil over a planar area and at specific depths of 0.0, 0.5, 2.5, 5.0, 10.0, and 50.0 g/cm 2 . On the basis of the results, we also derive the conversion coefficients for exponentially distributed volumetric sources. In addition, we obtain the conversion coefficients that give the effective dose accumulated over the first and second months, the first year, and over a lifetime (50 years) because of the contamination remaining on the ground. These calculations indicate that the conversion coefficients to obtain the effective dose rate are higher for the younger ages compared with adults, but do not exceed the ambient dose equivalent rate. Furthermore, we find that the difference between the calculated effective dose rates according to the International Commission on Radiological Protection 1990 and 2007 Recommendations is small (7% maximum) for a ground contamination of radioactive cesium.